Life at Extremes Environments, Organisms and Strategies for Survival - Bell, E. M.; Ebooks Corporation (Wallingford : CABI, 2012)
From arid deserts to icy poles, outer space to the depths of the sea, this exciting new work studies the remarkable life forms that have made these inhospitable environments their home. Covering not only micro-organisms, but also higher plants and animals such as worms, fish and polar plants, this book details the ecological, biological and biogeochemical challenges these organisms face and unifying themes between environments. Equally useful for the expert, student and casual scientific reader, this book also explores the impact of climate change, rapid seasonal changes and pollution on these extraordinary creatures. It is suitable for researchers and students of life sciences and ecology.
Contenido: 2.3.2 Embryophytes and the decline in atmospheric CO[sub(2)] and the rise of O[sub(2)]2.4 Mass Extinction and Extreme Environments; 2.4.1 Permian/Triassic (P/Tr) boundary; 2.4.2 Cretaceous/Tertiary (K/T) boundary (65 Ma); 2.5 Conclusion; References; 3 Polar Marine Ecosystems; 3.1 Introduction; 3.2 The Arctic Seas Versus the Southern Ocean; 3
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: ACLIMATACION; ADAPTACION (BIOLOGIA); AMBIENTES EXTREMOS; CAMBIOS CLIMATICOS; COMUNIDADES BIOTICAS; CONTAMINACION